Natureza humana como primeira imagem das relações internacionais : fundamentos filosóficos para teoria realista estruturalista de Kenneth Waltz - Barbosa, Camila Palhares (2017)
This paper aims to investigate the role of human nature to theoretical discourses of International Relations through the dialogue between the structural realism of Kenneth Waltz and social constructivism of Alexander Wendt. Insofar as the realism doctrine remains one of the most consolidate theory of International Relations and the structural proposal of Waltz is traditionally associate as the theory that withdraws the need of determinist axioms of human behavior to the understanding of International Relations, my proposal when using these authors is to demonstrate that philosophical bias discourses on human nature remain part of what we understand as International Relations theories. Furthermore, through this analysis I intent to shown that the need to stablishes the International Relations field as a separated from social and political sciences, remove interdisciplinary aspects of theoretical discourses, specially, in the structural realism proposed by Waltz.